Effect of solvent proton affinity on the kinetics of michael addition polymerization of n, n′‐bismaleimide‐4, 4′‐diphenylmethane with barbituric acid. Issue 3 (10th May 2013) - Yu, Fu‐En; Hsu, Jung‐Mu; Pan, Jing‐Pin; Wang, Tsung‐Hsiung; Chiang, Yu‐Ching; Lin, Winnie; Jiang, Jyh‐Chiang; Chern, Chorng‐Shyan
<x xml:space="preserve">Abstract</x> The effect of solvent proton affinity on the kinetics of the Michael addition polymerizations of N, N′‐bismaleimide‐4, 4′‐diphenylmethane (BMI) and barbituric acid (BTA) in different solvents [N‐methyl‐2‐pyrrolidone (NMP), N, N′‐dimethylacetamide (DMAC), and N, N′‐dimethylformamide (DMF)] were investigated. This was achieved by the complete suppression of the competitive free radical polymerization via the addition of a sufficient amount of hydroquinone (HQ). A mechanistic model was developed to adequately predict the polymerization kinetics before a critical conversion, at which point the diffusion‐controlled polymerization become the predominant factor during the latter stage of polymerization, was achieved. The activation energy (Ea) of the Michael addition polymerization of BMI with BTA in the presence of HQ in increasing order was: NMP < DMAC < DMF, which was correlated quite well with the solvent proton affinity (NMP > DMAC > DMF). By contrast, the frequency factor (A) in increasing order is: NMP < DMAC < DMF. As a result of the compensation effect between Ea and A, at constant temperature, the Michael addition rate constant decreased with increasing solvent proton affinity. POLYM. ENG. SCI., 54:559–568, 2014. © 2013 Society of Plastics Engineers